Educational expansion in the Netherlands: better chances for all?. (2nd January 2020) - Allen, Jim; Belfi, Barbara
ABSTRACT: Higher education in the Netherlands has expanded rapidly in the last two decades, giving rise to concerns about possible negative effects on educational quality and the labour market value of a higher education degree. In this paper, we use data from national graduate surveys and adult literacy surveys to explore this. While no evidence was found for a negative effect of the HE expansion on graduate skill levels or unemployment risk, real graduate earnings have decreased over the past two decades relative to those of post-secondary non-tertiary graduates. This does not seem to have been driven by a shift of HE graduates into non-graduate occupations, but rather by a general decline in relative earnings in jobs at all levels. Finally, the more adverse effects of the expansion were particularly apparent for graduates with lower grades, women and graduates with a non-western migration background. These findings indicate that, despite relatively low unemployment, the HE labour market is increasingly becoming a buyers' market. In this market, graduates with attributes that buyers want – males, native Dutch graduates, high-performers – emerge as relative winners of the educational expansion.